Numerical investigation of the effect of hot and cold fluids on dental implants made of different materials - Guzel, Saadet Pilten; Arpa, Ilknur; Can, Omer F.; Celik, Nevin (Elsevier, 2025)
An effective numerical method for analyzing components with extremely complicated geometry, stresses, and materials is finite element analysis (FEA), which is particularly useful for analyzing dental issues. Because of their shortcomings, FEA and related analysis techniques cannot offer conclusive answers. Clinical trials must be conducted to validate them. They are crucial for initial forecasts, nevertheless, especially in the planning stage prior to clinical trials. Therefore, the ultimate goal is to incorporate such technologies into clinical practice to help dentists in the diagnostic and treatment stages. In this study thermal effects of hot and cold fluids on five teeth in the jawbone, one of which is the main tooth and other four are dental implants, are estimated by use of FEA. Since a typical dental implant consists of an implant body, an abutment and a crown, the implant body and crown may be affected differently when they are made of different materials. Based on this reasoning, the cases where the implant body is made of titanium, zirconia, gold and cobalt and the crown is made of zirconia and porcelain are discussed numerically. It was considered as a positive criterion that the prosthetic implant duo, which was considered to be at body temperature at the beginning, were affected by the temperature under different thermal conditions. Therefore, as thermal conditions, the contact of cold (5 degrees C) and hot (60 degrees C) liquid beverages to the teeth and the effect of cold air (-10 degrees C) contacting to the teeth with the breath taken in a cold air are examined.
Keywords: Numerical solution; Titanium implants; Zirconia and porcelain crowns; Finite element analysis; Convection